Hydrogeochemical Characteristics and Evolution of Hot Springs in Eastern Tibetan Plateau Geothermal Belt, Western China: Insight from Multivariate Statistical Analysis. (4th June 2017) - Shi, Zheming; Liao, Fu; Wang, Guangcai; Xu, Qingyu; Mu, Wenqing; Sun, Xiaoyi
Abstract : The eastern Tibetan Plateau geothermal belt is one of the important medium-high temperature geothermal belts in China. However, less work has been done on the hydrochemical characteristic and its geological origin. Understanding the chemical characteristics and the hydrochemical evolution processes is important in evaluating the geothermal energy potential in this area. In the present study, we discussed the hydrochemical properties and their origins of 39 hot springs located in the eastern Tibetan Plateau geothermal belt (Kangding-Litang-Batang geothermal belt). Cluster analysis and factor analysis are employed to character the hydrochemical properties of hot springs in different fault zones and the possible hydrochemical evolution processes of these hot springs. Our study shows that the hot springs can be divided into three groups based on their locations. The hot springs in the first group mainly originate from the volcanic rock and the springs in the second group originate from the metamorphic rock while the springs in the third group originate from the result of mixture of shallow water. Water-rock interaction, cation exchange, and the water environment are the three dominant factors that control the hydrochemical evolution process in the eastern Tibetan Plateau. These results are also in well agreement with the isotopic and chemical analysis.